2020
DOI: 10.3390/act9030064
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Drag Reduction and Optimization of MIRA Model Based on Plasma Actuator

Abstract: Active flow control of surface dielectric barrier discharge (SDBD) plasma is a technology that converts electrical energy into kinetic energy to achieve flow control. Its main application areas are concentrated in the aviation field. Undoubtedly, few studies have applied it in the field of automobile flow control. Meanwhile, during high-speed driving, there is a serious airflow separation phenomenon at the rear of notch-back cars, which brings a large area of negative pressure to the back of the cars. Due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Many studies have shown the potential use of plasma actuators as flow control devices across a wide range of flow applications. Examples include control of transition to turbulence [8][9][10], drag reduction for highway vehicles [11][12][13], lift to drag ratio modification for flow over a wing [14,15], flow modification over bluff bodies [13,16], blade vortex interaction noise control [17], flight control for small aircrafts and projectiles [18,19] and deicing application [20][21][22]. However, environmental ruggedness and performance reliability of these actuators must be studied before their practical implementation for any external flow applications.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the potential use of plasma actuators as flow control devices across a wide range of flow applications. Examples include control of transition to turbulence [8][9][10], drag reduction for highway vehicles [11][12][13], lift to drag ratio modification for flow over a wing [14,15], flow modification over bluff bodies [13,16], blade vortex interaction noise control [17], flight control for small aircrafts and projectiles [18,19] and deicing application [20][21][22]. However, environmental ruggedness and performance reliability of these actuators must be studied before their practical implementation for any external flow applications.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the related topic of plasma actuators (PA) for flow control applications is widely studied [9][10][11][12][13][14][15][16][17][18][19][20], there is recently a growing interest in the study of surface dielectric barrier discharges (SDBDs) as an anti-icing and de-icing system [21][22][23][24][25][26][27][28][29][30]. Probably Meng et al [24] and Cai Jinsheng et al [21] were the first who reported experimental results indicating that SDBDs can work as an anti/de-icing system.…”
Section: Introductionmentioning
confidence: 99%
“…2b. This is a typical approach for simulating plasma actuators [21][22][23]. In principle, also a plasma model could be employed to actually calculate the ion wind as it is accelerated by the propagating streamers.…”
Section: Schlieren Diagnosticmentioning
confidence: 99%